2015
DOI: 10.1038/eye.2015.17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual field progression between temporally tilted disc and nontilted disc, in patients with normal tension glaucoma

Abstract: Purpose To investigate the long-term visual field (VF) progression of temporally tilted disc and nontilted disc in normal tension glaucoma (NTG). Methods Retrospective, observational case series. Forty-seven patients with temporally tilted disc (47 eyes), 44 patients with nontilted disc in NTG (44 eyes) patients, who were examined by at least 5 VF tests, and were followed-up over a 5-year period, at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Tilt ratio as a contributor to VFD progression has been still on debate. Namely, Lee et al 17 found that tilt ratio was not associated with VF progression rate, while Choy et al 18 reported there were more VFDs found in eyes with increasing tilt ratio. In our study, compared to typical glaucomatous VFD group, temporal VFD group had greater tilt ratio and its progression rate was slower.…”
Section: Discussionmentioning
confidence: 99%
“…Tilt ratio as a contributor to VFD progression has been still on debate. Namely, Lee et al 17 found that tilt ratio was not associated with VF progression rate, while Choy et al 18 reported there were more VFDs found in eyes with increasing tilt ratio. In our study, compared to typical glaucomatous VFD group, temporal VFD group had greater tilt ratio and its progression rate was slower.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between tilted disc and progression of glaucoma is poorly understood, especially regarding causal factors that impact it. However, it has been assumed that myopic eyes with a tilted disc reliably leads to stable progression of glaucoma compared with eyes that have a non-tilted disc after the elongation process is complete [21][22][23]. In other words, disease progression in myopic glaucoma patients with PS is more stable than those without PS.…”
Section: Discussionmentioning
confidence: 99%
“…21 Interestingly, tilted discs are also associated with decreased progression of primary open-angle and normal-tension glaucoma. 22,23 It is important to correct refractive error early in these patients to prevent amblyopia in asymmetric disease. 7 Although magnetic resonance imaging (MRI) may show the optic nerve inserting obliquely into the globe, 7 neuroimaging is not usually indicated.…”
Section: Tilted Discsmentioning
confidence: 99%